(untitled) (African Journal of Science, Technology and Social Sciences, 2024)
The study aimed to assess the influence resource planning influences the implementation of a faecal sludge management system in Embu County between March and December 2022, adopting a descriptive research design. The population included 655 individuals, with a sample size determined using Taro Yamane’s formula for landlords and a census method for top managers, technical officers, contractors, and individuals involved in exhausting. Research instruments comprised scheduled questionnaires and interviews, with ethical considerations obtained from relevant authorities. Data analysis utilized SPSS Version 26 for both qualitative and quantitative data, employing thematic analysis for qualitative data and descriptive and inferential analyses for quantitative data. Findings revealed a notable gender imbalance and age-related impacts on perceptions in fecal sludge management. Resource planning effectiveness indicated strengths in objective setting, communication, and risk management, significantly influencing system implementation. Recommendations include strengthening the strategic framework, enhancing vision and mission statements, refining financial planning, addressing role comprehension gaps, aligning resource planning with project timelines, and implementing regular monitoring and evaluation for ongoing improvements. Overall, the study emphasizes the pivotal role of resource planning in the success of fecal sludge management projects and highlights areas for improvement to enhance effectiveness.